2021
DOI: 10.1038/s41467-021-24295-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow-induced left-right asymmetric decay of Dand5 mRNA in the mouse embryo requires a Bicc1-Ccr4 RNA degradation complex

Abstract: Molecular left-right (L-R) asymmetry is established at the node of the mouse embryo as a result of the sensing of a leftward fluid flow by immotile cilia of perinodal crown cells and the consequent degradation of Dand5 mRNA on the left side. We here examined how the fluid flow induces Dand5 mRNA decay. We found that the first 200 nucleotides in the 3′ untranslated region (3′-UTR) of Dand5 mRNA are necessary and sufficient for the left-sided decay and to mediate the response of a 3′-UTR reporter transgene to Ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 50 publications
(75 reference statements)
3
63
0
Order By: Relevance
“…5D ). (4) The accompanying manuscript by Minegishi et al 44 demonstrates Bicc1 binding to the mouse Dand5 3′-UTR and identified specific binding motifs. Intriguingly, we found alike sequences in the Bicc1RE, which apparently were located within dS-tpMO or next to dL-tpMO target sequences that specifically impair translational repression in Xenopus (Figure S1B ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5D ). (4) The accompanying manuscript by Minegishi et al 44 demonstrates Bicc1 binding to the mouse Dand5 3′-UTR and identified specific binding motifs. Intriguingly, we found alike sequences in the Bicc1RE, which apparently were located within dS-tpMO or next to dL-tpMO target sequences that specifically impair translational repression in Xenopus (Figure S1B ).…”
Section: Discussionmentioning
confidence: 99%
“…Our work, together with complementing analyses in the mouse (cf. 44 ), constitutes a conceptual advance in our understanding of symmetry breaking, namely the flow-dependent activation of the RNA-binding protein Bicc1 to repress dand5 translation on the left LRO margin in a Dicer-dependent manner. Based on our analyses, we suggest a model schematically depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a, b; Supplementary Video 4): one to visualize perinodal immotile cilia, and the other to monitor the response to mechanical stimuli. Dand5 mRNA is the ultimate target of nodal flow 15, 16 , being degraded by the Bicc1-Ccr4 complex in response to the flow 17 . Crown cells were labeled with the NDE4-hsp-dsVenus-Dand5-3′-UTR transgene, with the level of dsVenus mRNA reflecting that of Dand5 mRNA 17 , whereas their immotile cilia were visualized with a transgene encoding mCherry.…”
Section: Mechanical Stimuli Administered To Immotile Cilia By Optical...mentioning
confidence: 99%
“…To establish transgenic lines in which KV-epithelial cells are specifically labelled, we cloned the 5-kb upstream sequence of zebrafish dand5 (Figure 1b). A previous transient promoter assay demonstrated that the upstream sequence of zebrafish dand5 drives the reporter expression around KV (Gourronc et al, 2007), but stable transgenic lines using the dand5 promoter have yet to be estab- This can be explained by the fact that 3' untranslated sequence of mouse dand5 is responsible for its right-sided expression (Minegishi et al, 2021;Nakamura et al, 2012). Untranslated sequences of zebrafish dand5, which are not included in the plasmid construct of this study, could have a similar function to that of mouse dand5.…”
Section: Establishment Of Dand5:egfp To Specifically Label Kv-epithel...mentioning
confidence: 85%